2022
DOI: 10.1002/ece3.9401
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and application of loop‐mediated isothermal amplification technique for sex identification in red‐whiskered bulbul (Pycnonotus jocosus)

Abstract: The red-whiskered bulbul (Pycnonotus jocosus) is a popular avian species in Thailand and many other countries. The red-whiskered bulbul has a high economic value, but breeding is challenging since sex identification is difficult. The PCR method is now used for sex identification. However, PCR amplification and post-PCR analysis neces-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…However, this method has some limitations: the accuracy of large-scale sex identification data using this method under field conditions is only 97.41% and affects the performance of the poultry in the later stages. Early sex identification of juvenile waterfowl has been achieved using PCR technology, with an accuracy of 100% ( Changtor et al, 2022 ). Molecular sequencing results showed that the CHD1-Z sequence length was 436 bp.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method has some limitations: the accuracy of large-scale sex identification data using this method under field conditions is only 97.41% and affects the performance of the poultry in the later stages. Early sex identification of juvenile waterfowl has been achieved using PCR technology, with an accuracy of 100% ( Changtor et al, 2022 ). Molecular sequencing results showed that the CHD1-Z sequence length was 436 bp.…”
Section: Discussionmentioning
confidence: 99%